A bill declaratory and explanatory of the meaning of the second section of an act in the Revised statutes, Chapter 36th, entitled, "Divorce and alimony." (House doc. (North Carolina. General Assembly. House of Commons) ;, 1852)
1852 House bill providing additional explanation of a section of the Divorce and Alimony act in the North Carolina Revised Statutes, Chapter 36. This bill provided grounds for divorce if a woman married a man while pregnant with other's child, and her spouse was unaware of the deception. The only exception was if the husband continued to live with the wife for more than six months after discovery of her situation.